Management options to alleviate the menace of rice (Oryza sativa) straw burning - An overview - PRASAD, RAJENDRA; SHIVAY, YASHBIR SINGH (The Indian Journal of Agricultural Sciences, 2018)
Burning of rice (Oryza sativa L.) straw in the states of Punjab, Haryana and western Uttar Pradesh in India has become an environmental and health hazard not only in the region, where it is practiced, but also in the surrounding states. It is responsible for thick smog in the months of November and December each year. This is due to a short (2-3 weeks) turn-over period between rice harvest and wheat sowing. Management options, such as, its incorporation in soil have not found favour with the farmers despite addition of plant nutrients and building soil fertility. Happy Seeder or Turbo Seeder, an equipment that cuts the rice stubbles left after the rice harvest by combines and spreads the straw asmulch after seeding wheat without primary tillage is being accepted by the farmers and gives higher yield of wheat as compared to traditional land preparation practices. Rice straw can profitably be used as mulch in vegetable crops and orchards. Its industrial uses include production of ethanol and paper. However, these technologies require heavy investment and specialist workers. A low cost industry of making rice straw-jute mattresses is suggested. Also it can be transported to meet the animal feed shortage in neighboring state of Rajasthan. However, the major problem with rice straw is its bulk and thus a large amount is to be removed within 2-3 weeks. This would require careful preparedness, planning and government intervention in providing necessary facilities in the way of railway bogies and special trains.